Recognition of Ergonomic Risks for Low Back Pain using the Nordic Body Map Method in Barbershop Workers: Rekognisi Risiko Ergonomi terhadap Low Back Pain dengan Metode Nordic Body Map pada Tenaga Pekerja Barbershop - Atika Zulhidah Hasan; Siti Ainun Ma'rufa (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Sore muscles and joints, especially the lower back, may be caused by unergonomic working postures. This includes standing for long periods of time. As a result of these complaints, the functional capacity of the lower back will decrease, resulting in a decrease in the productivity of workers, including workers in barbershops. The aim of this activity is to identify the ergonomics of barbershops and the incidence of low back pain. The Nordic Body Map questionnaire is used as an identification tool. The activity partners are 15 barbershop employees in the Rungkut area of ​​Surabaya. Data was obtained that these workers worked with an awkward posture for 4 hours. The findings were that the buttocks had the highest proportion of respondents rated "Not Painful" (40%), and the right hand was rated "Somewhat Painful" (66.7%). Respondents stated that the most severe pain was experienced in the right wrist (47%), and lower back (53%). From these findings it is known that barbershop workers do not have knowledge about the ergonomics of working positions, and have the potential to experience lower back pain. These findings can be used as a basis for follow-up community service activities to socialize aspects of ergonomics and physiotherapy.